Graphite powder and related material as the principal components of carbon plastic electrodes - Švancara, Ivan; Mikysek, Tomáš; Stočes, Matěj; Ludvík, Jiří (Nova Science Publishers, 2013)
In this chapter, graphite in powdered form is presented as the material of choice for the preparation and use of the so-called carbon paste electrodes (CPEs) representing one of the most popular types of electrodes in electrochemical measurements for more than five decades. Starting with a short historical reminiscence, when highlighting also the importance of carbon materials in electrochemistry as such, powdered graphite is presented as particularly suitable material for an endless variety of electrodes, sensors, and detectors; the individual forms having found the widespread use in theoretical electrochemical studies, practical electro analysis, as well as in other instrumental measurements. Special attention is paid to the graphite powder with respect to its applicability in carbon paste mixtures and, subsequently, in the configuration of CPEs. In this respect, classification of traditional types of graphite powders is also given, completed with a survey of related and/or alternate carbonaceous materials whose applicability to the preparation of CPEs has undergone a real boom in the new millennium and, in fact, resulted in a new renaissance of the field. Furthermore, graphite powders (together with related materials) are discussed via physical, physicochemical, and principal electrochemical properties and of similar interest are also the corresponding graphite/carbon paste mixtures, including the experimental know-how on their laboratory preparation and way(s) of housing in specially designed holders and similar assemblies At the end of this section, one special example is included, summarizing for the first time the recently performed studies on less well-known phenomena within the electrochemistry with CPEs – the ohmic resistance of carbon pastes in relation with their structure and behavior. Last but not least, the electrochemistry and electroanalysis with CPEs are briefly surveyed, documenting the versatility of these electrodes in modern instrumental analysis, their adaptability to the present day’s trends, as well as great potential in the future, regardless whether one considers traditional graphite powder-based configurations or mixtures from new alternate materials.
Keywords: graphite powder; carbon paste electrodes; carbon materials; electrochemistry